Implementasi Solusi Teknologi untuk Pelayanan Kesehatan Lansia: Desain Tongkat Arduino dan Aplikasi Rekam Medis - Lawi, Ansarullah; Hernando, Luki; Putera, Dimas Akmarul; Salimah, Nora; Surgiwe, Surgiwe (Jurnal SOLMA, 2024)
Background: As the number of elderly individuals in Indonesia increases, the challenges in providing effective and efficient healthcare services become increasingly complex. One of the main issues faced by the elderly is the risk of falls due to limited mobility and declining physical performance. Additionally, the lack of integrated medical record management often hinders the timely and accurate delivery of medical services. This Community Service program aims to implement technological solutions in elderly care through the development of a smart cane (LansiaTracker) and a medical record application (LansiaCare). The smart cane (LansiaTracker) is equipped with various sensors to detect the user's physical condition, provide early warnings of fall risks, and monitor daily activities. Furthermore, the integrated medical record application (LansiaCare) allows for real-time management of the elderly's health data, making relevant health information easily accessible to family members and medical staff. Method: Socialization, training, and assistance for the elderly at Puskesmas Tiban Baru, aiming to enhance their quality of life and reduce health risks. Results: The use of the smart cane (LansiaTracker) and the medical record application (LansiaCare) not only effectively supports the mobility of the elderly but also improves their overall health monitoring. Conclusion: The implementation of this technology provides practical and affordable solutions for various elderly communities, especially those with limited access to healthcare facilities, enhancing responsiveness in emergency situations and facilitating comprehensive medical data recording and management.